Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan Koperasi Simpan Pinjam Swamitra Mitra Bahari Tegal - Asih Setyaningsih; Roni; Andi Yulianto; Slamet Bambang Riono; Dwi Harini (Journal of Accounting and Finance (JACFIN), 2021)
This research is entitled financial ratio analysis to assess the financial performance of the Swamitra Mitra Bahari Tegal savings and loan cooperative. The purpose of this study is to determine the financial performance of the Swamitra Mitra Bahari Tegal savings and loan cooperative regarding the assessment of financial performance. This research method uses quantitative descriptive research. The population in this study is the financial statements of the Swamitra Mitra Bahari Tegal savings and loan cooperative, with the sample taken is the cooperative's financial statements for the last two years, namely 2020 and 2021. The result of this study is that the liquidity ratio and solvency ratio in the Swamitra Mitra Bahari Tegal savings and loan cooperative in 2020 to 2021 are included in the bad criteria. The rentability ratio in the ROA analysis results in 2020 is included in the less good criteria and in 2021 it is included in the criteria is quite good, while the ROE analysis results in 2020 are included in the good criteria and in 2021 it is included in the excellent criteria.